Plasma-derived small extracellular vesicles unleash the angiogenic potential in head and neck cancer patients - Tengler, Luisa; Schütz, Julia; Tiedtke, Moritz; Jablonska, Jadwiga; Theodoraki, Marie-Nicole; Nitschke, Katja; Weiß, Christel; Seiz, Elena; Affolter, Annette; Jungbauer, Frederic; Lammert, Anne; Rotter, Nicole; et al. (Molecular medicine, 2023)
In Head and neck cancer (HNC) angiogenesis is essential for tumor progression and metastasis. Small extracellular vesicles (sEVs) from HNC cell lines alter endothelial cell (EC) functions towards a pro-angiogenic phenotype. However, the role of plasma sEVs retrieved from HNC patients in this process is not clear so far. Plasma sEVs were isolated on size exclusion chromatography columns from 32 HNC patients (early-stage UICC I/II: 8, advanced-stage UICC III/IV: 24), 12 patients with no evident disease after therapy (NED) and 16 healthy donors (HD). Briefly, sEVs were characterized by transmission electron microscopy (TEM), nanoparticle tracking analysis (NTA), BCA protein assays and Western blots. Levels of angiogenesis-associated proteins were determined using antibody arrays. The interaction of fluorescently-labeled sEVs with human umbilical vein ECs was visualized by confocal microscopy. The functional effect of sEVs on tubulogenesis, migration, proliferation and apoptosis of ECs was assessed. The internalization of sEVs by ECs was visualized using confocal microscopy. Based on antibody arrays, all plasma sEVs were enriched in anti-angiogenic proteins. HNC sEVs contained more pro-angiogenic MMP-9 and anti-angiogenic proteins (Serpin F1) than HD sEVs. Interestingly, a strong inhibition of EC function was observed for sEVs from early-stage HNC, NED and HD. In contrast, sEVs from advanced-stage HNC showed a significantly increased tubulogenesis, migration and proliferation and induced less apoptosis in ECs than sEVs from HD. In general, plasma sEVs carry a predominantly anti-angiogenic protein cargo and suppress the angiogenic properties of ECs, while sEVs from (advanced-stage) HNC patients induce angiogenesis compared to HD sEVs. Thus, tumor-derived sEVs within the plasma of HNC patients might shift the angiogenic switch towards angiogenesis.
Gesehen am 12.08.2024